Analiza nawyków i zachowań związanych ze stosowaniem leków oryginalnych i generycznych = The analysis of behaviour related to the use of original and generic drugs - Kozłowski, Piotr; Streit, Dominika; Kozłowska, Magdalena (Journal of Education, Health and Sport, 2015)
Kozłowski Piotr, Streit Dominika, Kozłowska Magdalena. Analiza nawyków i zachowań związanych ze stosowaniem leków oryginalnych i generycznych = The analysis of behaviour related to the use of original and generic drugs. Journal of Education, Health and Sport. 2015;5(8):27-35. ISSN 2391-8306. DOI 10.5281/zenodo.22392 http://dx.doi.org/10.5281/zenodo.22392 https://pbn.nauka.gov.pl/works/600221 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-b6702994-564a-4e79-8873-852a7206eecb http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A27-35 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. ANALIZA NAWYKÓW I ZACHOWAŃ ZWIĄZANYCH ZE STOSOWANIEM LEKÓW ORYGINALNYCH I GENERYCZNYCH The analysis of behaviour related to the use of original and generic drugs Piotr Kozłowski1, Dominika Streit2, Magdalena Kozłowska3 1Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie 2Uniwersytet Medyczny w Lublinie 3Katedra i Klinika Neurologii, UM w Lublinie Uniwersytet Medyczny w Lublinie ul. Aleje Racławickie 1, Lublin e-mail: piotr7176@gmail.com Abstrakt Celem pracy była ocena zachowań i nawyków a także poziom wiedzy na temat leków generycznych. Badaniem objęto 108 osób. W grupie badanej kobiety stanowiły 67,6% respondentów, natomiast mężczyźni 32,4%. Wiek ankietowanych zawierał się w przedziale od 20 do 60 lat. Badanie przeprowadzono w okresie od stycznia do lutego 2015 roku metodą wywiadu standaryzowanego. Narzędziem badawczym, którym posłużono się do zebrania danych, był autorski kwestionariusz, który zawierał 29 pytań z możliwością jednokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi-kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Najbardziej istotnym elementem dla ankietowanych wpływającym na wybór lek była jego cena. Istniała różnica biorąc pod uwagę płeć respondenta gdyż uwagę na cenę zwracało 58,9% kobiet i 37,1% mężczyzn. Większość ankietowanych (60,2%) nigdy nie została zapytana przez lekarza odnośnie preferencji dotyczących ceny leku. Jedna trzecia respondentów (32,4%) nigdy nie była zapytana przez farmaceutę o chęć kupna tańszego odpowiednika. Większość osób z grupy badanej (69,4%) zawsze lub sporadycznie wybierała kupno leku generycznego nawet jeżeli w aptece dostępny jest lek oryginalny. Analizie i ocenie została poddana również wiedza na temat leków oryginalnych i generycznych. Zdaniem jednej trzeciej (34,3%) ankietowanych nie było różnicy w działaniu pomiędzy lekami generycznymi a oryginalnymi. Respondenci zapytani czy obie grupy leków maja ten sam skład w 50,9% nie znali odpowiedzi na to pytanie. Słowa kluczowe: leki generyczne, leki odtwórcze, generyk. Abstract The aim of the study was an evaluation of behaviours and habits, as well as an essesment of the level of knowledge about generic drugs. The study included 108 people. In the study group, women accounted for 67.6% of respondents, while 32.4% were men. The age of the respondents ranged from 20 to 60. The study was conducted in the period from January to February 2015 and it employed standardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 29 questions multiple-choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. For the participants, the most important factor influencing the choice of particular drug was the price of the product. The difference was related to gender as 58.9% of female and only 37.1% male respondents agreed on the relevance of the price. The majority of the respondents (60.2%) had never been asked by a pharmacist about their price-dependent preferences. One third of the respondents (32.4%) had never been offered a cheaper generic equivalent for a brand-name drug. Most participants of the study (69.4%) always or occasionally chose to buy a cheaper generic equivalent fro a brand-name drug. The participants knowledge about original and generic drugs was also analysed and evaluated. According to one third (34.3%) of the respondents the generic products had effects identical to the original drugs. Being asked if the two groups products have the same composition, 50.9% of respondents did not know the answer. Key words: generic drug, generics.